ANALISIS SISTEM TIME CHARTER DAN FREIGHT CHARTER ATAS REVENUE TERHADAP OPERATING PROFFIT MARGIN DENGAN OPERATIONAL COST SEBAGAI MEDIASI PADA PT. BINTANG SAMUDERA MANDIRI LINES Tbk - Arifah Ahsani Taqwim; Nofrisel, Nofrisel; M. Iqbal Firdaus; Sandriana Marina; Dian Artanti Arubusman (LPSDI Bina Patria, 2025)
This study aims to determine the effect of revenue on Operating Profit Margin with Operational Cost as a mediator through the time charter and freight charter systems at PT. Bintang Samudera Mandiri Lines Tbk (BSML). The research method used is quantitative and associated with the company's secondary data. The study population includes Revenue Time Charter, Freight Charter, Operational Cost, and Operating Profit Margin at PT. Bintang Samudera Mandiri Lines Tbk from 2020. The sample consists of monthly data from January 2020 to December 2022, with 36 samples from 5 company vessels. The path analysis method is used with the help of SPSS Ver. 26 software. The study results show a positive and significant effect between Revenue and Operational Cost on the Time Charter and Freight Charter systems. Revenue also has a positive and significant effect on Operating Profit Margin in both systems. However, Operational Cost only has a positive and significant effect on Operating Profit Margin in the Freight Charter system. Indirectly, Revenue through Operational Cost affects the Operating Profit Margin in the Freight Charter system, but not in the Time Charter system. There is a significant difference between Revenue, Operational Cost, and Operating Profit Margin generated by the two systems at PT. Bintang Samudera Mandiri Lines Tbk. With the implication that the company must ensure that the increase in revenue is followed by operational cost efficiency by the company's management.